Construction of AMPK-related circRNA network in mouse myocardial ischemia–reperfusion injury model - Yang Song; Yi Zhao; Xiaodi Zhang; Cheng Cheng; Haidong Yan; Daxing Liu; Dengshen Zhang (BMC Cardiovascular Disorders)
Abstract Objective To screen Myocardial ischemia–reperfusion Injury in mice. adenosine monophate-activatedprotein kinase (AMPK) -related differentially expressed circularRNA (circRNA) in MIRI model, Ampk-related circRNA network was drawn to provide possible ideas for the prevention and treatment of MIRI. Methods The mouse MIRI model was constructed by ligation of the left anterior descending artery. After the model was successfully established, the related indicators of cardiac function were detected, and high-throughput sequencing was performed on the myocardial tissue of the mice. Results MIRI model was successfully constructed, and two AMPK related differentially expressed loops (novel_circ_043550 and novel_circ_035243) were screened out. A circRNA-miRNA-mRNA network consisting of 2 circRNA, 28 microRNA(miRNA) and 229 messengerRNA (mRNA) was constructed. Conclusions This study reveals the differential expression of several AMPK-related circRNAs in MIRI in mice, and the AMPK-related circRNA regulatory network is constructed, suggesting that AMPK-related circRNA may have potential clinical application prospects as a potential molecular marker and therapeutic target for MIRI.